Favorable prognosis in segmental vitiligo of the child. - Tagliavanti, M. (European Journal of Pediatric Dermatology, 2018)
In our pediatric cases, segmental vitiligo has the same incidence of non-segmental form (2) but its prognosis in the child is better than non-segmental one. As the current case seems to indicate the segmental form rarely turn into in the non-segmental form; moreover, the segmental form rarely tends to progress as extension over the years; on the other hand, it tends to spontaneously regress with time and is therefore more sensitive to the different therapies. The current case also underlines the association between vitiligo and atopic dermatitis; the great frequency of the latter in the child, however, makes it difficult to establish a causal association between the two diseases. Atopic dermatitis associated with vitiligo tends to save vitiliginous skin by spreading to its periphery or otherwise to healthy skin, probably due to the different T-lymphocyte response in the two diseases (1).